Pectin Metabolism and Assembly in the Cell Wall of the Charophyte Green Alga Penium margaritaceum. Issue 1 (20th March 2014) - Domozych, David S.; Sørensen, Iben; Popper, Zoë A.; Ochs, Julie; Andreas, Amanda; Fangel, Jonatan U.; Pielach, Anna; Sacks, Carly; Brechka, Hannah; Ruisi-Besares, Pia; Willats, William G.T.; Rose, Jocelyn K.C.
Abstract : The charophyte green alga Penium margaritaceum possesses an experimentally tractable pectin domain in its cell wall that offers insight into wall assembly and polar growth in plants . Abstract: The pectin polymer homogalacturonan (HG ) is a major component of land plant cell walls and is especially abundant in the middle lamella. Current models suggest that HG is deposited into the wall as a highly methylesterified polymer, demethylesterified by pectin methylesterase enzymes and cross-linked by calcium ions to form a gel. However, this idea is based largely on indirect evidence and in vitro studies. We took advantage of the wall architecture of the unicellular alga Penium margaritaceum, which forms an elaborate calcium cross-linked HG -rich lattice on its cell surface, to test this model and other aspects of pectin dynamics. Studies of live cells and microscopic imaging of wall domains confirmed that the degree of methylesterification and sufficient levels of calcium are critical for lattice formation in vivo. Pectinase treatments of live cells and immunological studies suggested the presence of another class of pectin polymer, rhamnogalacturonan I, and indicated its colocalization and structural association with HG . Carbohydrate microarray analysis of the walls of P. margaritaceum, Physcomitrella patens, and Arabidopsis ( Arabidopsis thaliana ) further suggested the conservation of pectin organization and interpolymer associations in the walls of green plants. The individual constituent HG polymers also have a similar size and branched structure to those of embryophytes. The HG -rich lattice of P. margaritaceum, a member of the charophyte green algae, the immediate ancestors of land plants, was shown to be important for cell adhesion. Therefore, the calcium-HG gel at the cell surface may represent an early evolutionary innovation that paved the way for an adhesive middle lamella in multicellular land plants.